Impact of lensing of gravitational waves on the observed distribution of neutron star masses - Sofia Canevarolo; Loek van Vonderen; Nora Elisa Chisari (The Open Journal of Astrophysics)
The distribution of masses of neutron stars, particularly the maximum mass value, is considered a probe of their formation, evolution and internal physics (i.e., equation of state). This mass distribution could in principle be inferred from the detection of gravitational waves from binary neutron star mergers. Using mock catalogues of $10^5$ dark sirens events, expected to be detected by Einstein Telescope over an operational period of $\sim1\, \rm year$ , we show how the biased luminosity distance measurement induced by gravitational lensing affects the inferred redshift and mass of the merger. This results in higher observed masses than expected. Up to $2%$ of the events are predicted to fall above the maximum allowed neutron star mass depending on the intrinsic mass distribution and signal-to-noise ratio threshold adopted. The underlying true mass distribution and maximum mass could still be approximately recovered in the case of bright standard sirens.